Essential oils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Volatile oil crops edited by Robert Hay and Peter Waterman 1993 185pp ISBN 0 582 07867 9 Hbk Longman Group UK Ltd PO Box 88, Fourth Avenue Harlow, Essex CM19 5AA, UK